Grief and resilience: The individual emotional transformation in Kanae Minato’s Confessions - Naufal Adrian Bastomi; Zuhrul Anam (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This paper explores the emotional transformation of Yuko Moriguchi, the central character in Kanae Minato's Confessions, following the sudden loss of her daughter. Utilizing Elisabeth Kübler-Ross's Five Stages of Grief and Sigmund Freud's theory of defense mechanisms, the study investigates how grief manifests and evolves into various emotional and psychological states. Employing a qualitative descriptive approach, the research uses literary analysis to trace Yuko's journey through denial, anger, bargaining, depression, and acceptance, alongside the deployment of defense mechanisms such as denial, repression, rationalization, sublimation, and projection. The findings reveal that the trauma causing sorrow is experienced in accordance with the five stages of grief, and successfully channels this sadness into behaviors that do not harm and are acceptable to society. The paper concludes that Moriguchi's actions reflect a human struggle for emotional transformation and survival after trauma.